The Candida albicans virulence factor candidalysin polymerizes in solution to form membrane pores and damage epithelial cells - Russell, Charles M; Schaefer, Katherine G; Dixson, Andrew; Gray, Amber LH; Pyron, Robert J; Alves, Daiane S; Moore, Nicholas; Conley, Elizabeth A; Schuck, Ryan J; White, Tommi A; Do, Thanh D; King, Gavin M; et al. (eLife, 2022)
Candida albicans causes severe invasive candidiasis. C. albicans infection requires the virulence factor candidalysin (CL) which damages target cell membranes. However, the mechanism that CL uses to permeabilize membranes is unclear. We reveal that CL forms membrane pores using a unique mechanism. Unexpectedly, CL readily assembled into polymers in solution. We propose that the basic structural unit in polymer formation is a CL oligomer, which is sequentially added into a string configuration that can close into a loop. CL loops appear to spontaneously insert into the membrane to become pores. A CL mutation (G4W) inhibited the formation of polymers in solution and prevented pore formation in synthetic lipid systems. Epithelial cell studies showed that G4W CL failed to activate the danger response pathway, a hallmark of the pathogenic effect of CL. These results indicate that CL polymerization in solution is a necessary step for the damage of cellular membranes. Analysis of CL pores by atomic force microscopy revealed co-existence of simple depressions and more complex pores, which are likely formed by CL assembled in an alternate oligomer orientation. We propose that this structural rearrangement represents a maturation mechanism that stabilizes pore formation to achieve more robust cellular damage. To summarize, CL uses a previously unknown mechanism to damage membranes, whereby pre-assembly of CL loops in solution leads to formation of membrane pores. Our investigation not only unravels a new paradigm for the formation of membrane pores, but additionally identifies CL polymerization as a novel therapeutic target to treat candidiasis.
Keywords: atomic force microscopy; native mass spectrometry; mass photometry